(untitled) (Journal of Atomic and Molecular Sciences, 2011)
We calculate the spectra and oscillator strengths for highly ionized cobalt-like Cd^21+ ions 3p^63d^9-3p^53d^10, 3p^63d^9-3p^63d^84p transitions by using multi-configuration self-consistent field method program together with fitting formula proposed by us. The calculations have a good agreement with observations.